Breast Cancer Imaging Using the Near-Infrared Fluorescent Agent, CLR1502 - Melissa L. Korb; Jason M. Warram; Joseph Grudzinski; Jamey Weichert; Justin Jeffery; Eben L. Rosenthal (Molecular Imaging)
Positive margins after breast conservation surgery represent a significant problem in the treatment of breast cancer. The near-infrared fluorescence agent CLR1502 (Cellectar Biosciences, Madison, WI) was studied in a preclinical breast cancer model to determine imaging properties and ability to detect small islands of malignancy. Nude mice bearing human breast cancer flank xenografts were given a systemic injection of CLR1502, and imaging was performed using LUNA (Novadaq Technologies Inc., Richmond, BC) and Pearl Impulse (LI-COR Biosciences, Lincoln, NE) devices. Normal tissues were examined for fluorescence signal, and conventional and fluorescence histology was performed using the Odyssey scanner. Peak tumor to background ratio occurred 2 days after injection with CLR1502. The smallest amount of tumor that was imaged and detected using these devices was 1.9 mg, equivalent to 1.9 × 10 6 cells. The highest fluorescence signal was seen in tumor and normal lymph node tissue, and the lowest fluorescence signal was seen in muscle and plasma. Human breast cancer tumors can be imaged in vivo with multiple optical imaging platforms using CLR1502. This pilot study supports further investigations of this fluorescent agent for improving surgical resection of malignancies, with the goal of eventual clinical translation.